The Influence Of Business Competence, Creativity, And Innovation On The Success Of The Bead Craft Industry In Tutul Village, Balung District, Jember Regency - Siska Ayu Nur Azizah; Haris Hermawan; Wahyu Eko Setianingsih (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
Business is one of the important sectors in driving economic growth in communities, especially in rural areas. In this context, business development is not only determined by external factors, but also by internal factors such as business competence, creativity, and innovation possessed by business actors. This study aims to determine and analyze the influence of business competence, creativity, and innovation on the success of the bead craft industry in Tutul Village, Balung District, Jember Regency. This type of research uses a quantitative method with a sample of 57 respondents. The sampling technique uses a saturated sampling method because the entire population is sampled. The main instrument in data collection is a questionnaire. Data analysis techniques used include validity tests, reliability tests, classical assumption tests, multiple linear regression, hypothesis tests (t-test and F-test), and the coefficient of determination (R²). The results of the analysis indicate that business competence, creativity, and innovation have a significant influence on the success of the bead craft industry in Tutul Village. The results of the coefficient of determination (R²) test indicate that these three variables contribute 76.8% to business success.